2000
DOI: 10.1210/endo.141.12.7950
|View full text |Cite
|
Sign up to set email alerts
|

Differential Pituitary Gene Expression Profiles Associated- To Aging and Spontaneous Tumors as Revealed by cDNA Expression Array

Abstract: Aging of the rat pituitary is often accompanied by the occurrence of adenomas. We asked whether complementary DNA hybridization array was adapted to identify gene expression patterns linked to aging and associated spontaneous adenomas. Thus, [32P]dATP-labeled cDNAs were prepared from pituitaries of three month-old rats (Y) and tumor-bearing 20-28-month-old rats (OT). The cDNAs were hybridized to identical membrane arrays allowing to study simultaneously 588 known genes (Clontech 7738-1). Among the 79 genes det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2001
2001
2006
2006

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 0 publications
2
17
0
Order By: Relevance
“…Bisphenol A and nonylphenol stimulate hydroxy radical generation in the rat striatum (Obata, 2000). Taken together, neonatal treatment with phenols can cause neuronal cell death by stimulating hydroxy radical formation, as seen in the effects of 6-OHDA (Ferger, 2001), and 1-methyl-4-phenylpyridinium ion (MPP/) (Obata, 2001 (Swanson, 1998;Volkow, 2002 (Camerer, 2000;Cho, 2002;Goidin, 2000;Hester, 2003). To investigate the long-lasting effects of neonatal treatments, we measured gene expression at 8 weeks of age, although the hyperactivity caused by 6-OHDA lesions might be attenuated to control levels (Zhang, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…Bisphenol A and nonylphenol stimulate hydroxy radical generation in the rat striatum (Obata, 2000). Taken together, neonatal treatment with phenols can cause neuronal cell death by stimulating hydroxy radical formation, as seen in the effects of 6-OHDA (Ferger, 2001), and 1-methyl-4-phenylpyridinium ion (MPP/) (Obata, 2001 (Swanson, 1998;Volkow, 2002 (Camerer, 2000;Cho, 2002;Goidin, 2000;Hester, 2003). To investigate the long-lasting effects of neonatal treatments, we measured gene expression at 8 weeks of age, although the hyperactivity caused by 6-OHDA lesions might be attenuated to control levels (Zhang, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…In carefully designed studies that take into account of these multiple variables, these experiments generate reliable data pertaining to genome-wide transcript expression (Draghici et al 2006). three studies have applied this analysis to the study of rodent pituitary adenomas (Goidin et al 2000, Wood et al 2002, Mohammed et al 2004b. In the three studies of human pituitary tumours, expression profiles were compared with that obtained from normal pituitary gland.…”
Section: Genome-wide Microarray Analysis Of Pituitary Tumoursmentioning
confidence: 99%
“…Three studies of pituitary tumours in animal models have exploited whole genome microarray analysis (Goidin et al 2000, Wood et al 2002, Mohammed et al 2004b. In comparison to gene expression profiling of human tumours, these studies, by their nature, are better controlled and have yielded useful data.…”
Section: Gene Expression Profiling and Animal Modelsmentioning
confidence: 99%
“…We propose that some additional growth factors might have been removed or replaced in older animals or that the continuous supply of galanin may disrupt an intracellular signal transduction system. Interestingly, it has been reported that the rat pituitary galanin gene expression profile is associated with aging and spontaneous tumours (Goidin et al 2000). Previous animal Figure 5 PRL serum levels in male and female, transgenic and non-transgenic animals.…”
Section: Figurementioning
confidence: 98%